Effect of Pleomorphic Adenoma Gene 1 Deficiency on Selected Behaviours in Adult Mice. (10th February 2021) - Tran, Stephanie C.; Jaehne, Emily J.; Dye, Laura E.; Wong, Joanne; Bakas, Jana S.; Gasperoni, Jemma G.; Hale, Matthew W.; van den Buuse, Maarten; Dworkin, Sebastian; Grommen, Sylvia V.H.; De Groef, Bert
Graphical abstract: Highlights: Loss-of-function mutations of PLAG1 causes Silver-Russell syndrome; PLAG1 is abundantly expressed in the murine brain. Circadian activity levels and various other behaviours are not affected by PLAG1 deficiency in mice. The responses of PLAG1 knockout mice in sound-based behavioural tests suggest a hearing impairment. Abstract: The proto-oncogene pleomorphic adenoma gene 1 ( Plag1 ) encodes a zinc finger transcription factor. PLAG1 is part of the high motility group AT hook-2 (HGMA2)–PLAG1–insulin-like growth factor 2 (IGF2) pathway that, when disrupted, leads to Silver–Russell syndrome, a severe form of intrauterine growth restriction. With little known about PLAG1's role in normal physiology, this study is the first to characterise the behavioural phenotype of PLAG1-deficient mice. Mice were tested for differences in circadian locomotor activity and body temperature, sleep-like behaviour, anxiety-like behaviour, cognition, social behaviour, and sensorimotor gating. Overall, the behavioural phenotype of the Plag1 knock-out (KO) mice was mild: no significant differences were seen in circadian activity levels, locomotion, object recognition, spatial memory or sociability compared to wild-type mice. However, the cued test of fear conditioning, prepulse inhibition of the startle response and Preyer's reflex test suggest that Plag1 KO mice may have a hearing impairment. This implies that PLAG1 plays an important role in proper functioning and/or development of the neural circuitry behind the auditory processes or interacts with genes involved in those processes.